Digital-Based Hybrid Learning in Mathematics - Orpilla, Jon-Jon; Oredina, Nora (Journal of Interdisciplinary Perspectives, 2025)
The integration of traditional face-to-face instruction with digital-based learning platforms in Mathematics remains underexplored, particularly in developing high-impact learning outcomes. This study assessed the effectiveness of digital-based hybrid learning in Mathematics through the development and validation of a mobile application, Smartmathics. Utilizing a Research and Development (R&D) approach and the ADDIE model, the study employed a Solomon four-group design with 120 learners. Results indicate Smartmathics as highly valid and highly acceptable, significantly improving academic performance compared to traditional methods. Notably, experimental groups exposed to digital-based hybrid learning demonstrated substantial progress, suggesting its potential to enhance learning outcomes and bridge understanding gaps. This innovative approach underscores the transformative power of technology in education, offering dynamic platforms for deeper comprehension and higher achievement levels in Mathematics.